Does it take two? The effect of partners' characteristics on teenage pregnancy - Madeline Zavodny (Federal Reserve Bank of Atlanta, 2000)
Although the determinants of whether a teenage woman has a nonmarital pregnancy and how such a pregnancy is resolved have been widely investigated, little is known about the joint influence of both partners' characteristics on nonmarital teenage pregnancy. This paper uses data from the 1995 National Survey of Family Growth to examine whether the characteristics of teenage women and their partners affect the likelihood of a nonmarital pregnancy and whether a pregnancy ends in abortion, marriage, or a nonmarital birth. The results indicate that several attributes of both men and women appear to play a role in nonmarital teenage pregnancy and its outcome. The estimated relationships between one partner's attributes and the probability of a nonmarital pregnancy and its resolution are generally little affected by whether the other partner's characteristics are also taken into account.
Keywords: 330